The Effects of Iraq Natural Asphalt on Mechanical Properties of Bituminous Hot Mixtures - Erkus, Yunus; Kok, Baha Vural; Yilmaz, Mehmet (Turkish Chamber Civil Engineers, 2022)
The increasing rate of traffic every day requires the roads to be made more stable. To improve the low and high temperature properties of the bituminous mixtures forming the coating layer of the flexible pavements, the binder in the mixture is often modified with various polymers. The most commonly used polymer in the modification is styrene-butadiene-styrene (SBS). However, SBS, which is very successful in improving the mechanical properties of the mixtures, is expensive and has brought the search for cheaper alternative additives. In this context, natural asphalts (NA) which are not subjected to any processes are used as additive. In this study, natural asphalt obtained from Zaho region of Iraq was used in 20%, 35% and 50% of bitumen modification by weight. The mechanical properties of mixtures prepared with different amount of NA modified bitumen were compared with 4% SBS modified bituminous mixtures. As a result, NA modification significantly improved the properties of bituminous mixtures. In particular, above 35% NA, the mixtures exhibited a superior performance by significantly resisting the effect of repeated loads. It was found that an average of 17.3% NA modification exhibited similar behaviour with 4% SBS modification and provided significant economic savings.
Keywords: Natural asphalt; SBS; modification; mechanical properties; mixture